Pengaruh Penambahan Chemical Agent Terhadap Angka Gula Reduksi Nira Perahan Pertama (NPP) - Siska Nuri Fadilah; Reswara Musyafa; Lutfi Nanda Putri; Dirgantara Syahril; Achri Isnan Khamil; Maktum Muharja (Universitas Trunojoyo Madura, 2023)
One of the critical problems in the sugar industry is the high number of reducing sugars due to the inversion of sucrose in sugarcane due to the presence of Leuconostoc sp. This study aims to determine the effect and the optimum conditions for adding chemical agents to the number of reducing sugars in the first milking juice (NPP). The chemical agents used were benzalkonium chloride, sodium metabisulfite, and calcium hypochlorite with variations of 1, 2, 3, and 4 g/L. Analysis of reducing sugar (%GR) using the Lane-Eynon test method. The results showed that the addition of chemical agents had an effect on decreasing %GR of NPP, but at low doses there was an increase in %GR. The optimum point was reached when the addition of 3g/L benzalkonium chloride + sodium metabisulfite (BKC+SMB) was able to reduce %GR up to 2.16%. This condition has the potential to provide a net profit of sugar production of Â±Rp. 14,056,000.00 per day. The use of BKC+SMB is a solution to reduce the number of reducing sugars and increase the yield value of the sugar industry.